Phase noise and squeezing spectra of the output field of an optical cavity containing an interacting Bose–Einstein condensate. (28th June 2016) - Dalafi, A; Naderi, M H
Abstract: We present a theoretical study of the phase noise, intensity and quadrature squeezing power spectra of the transmitted field of a driven optical cavity containing an interacting one-dimensional Bose–Einstein condensate. We show how the pattern of the output power spectrum of the cavity changes due to the nonlinear effect of atomic collisions. Furthermore, it is shown that due to a one-to-one correspondence between the splitting of the peaks in the phase noise power spectrum of the cavity output field and the s -wave scattering frequency of the atom–atom interaction, one can measure the strength of interatomic interaction. In addition, we show how the atomic collisions affect the squeezing behavior of the output field.